2012
DOI: 10.5923/j.materials.20120205.02
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Controlled in the Aggregative Growth of Strontium Carbonate Microcrystals

Abstract: The in fluence of PABA(p-aminobenzoicacid) and HEEDTA (N-(2-hydro xyethyl) ethylenediamine-N, N, Ntriacetic acid) on Strontionite crystals via simp le CO 2 d iffusion route is described. The results showed that the experimental parameters have great influence on the shape evolution of products. The presence of templating species and varied pH are the key prima ry conditions for the g rowth morphology. Spike like crystals self assembled in the form o f flo wer like and cauliflower shaped cluster with high cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The band centered at 3425 cm À1 corresponds to the n(OH) stretching vibration of the surface adsorbed water molecules. 30,31…”
Section: Sem/eds and Tem Analysesmentioning
confidence: 99%
“…The band centered at 3425 cm À1 corresponds to the n(OH) stretching vibration of the surface adsorbed water molecules. 30,31…”
Section: Sem/eds and Tem Analysesmentioning
confidence: 99%
“…The band at 1472 cm −1 corresponds to the asymmetric stretching mode of the C−O bond, while the sharp bands at 858 and 704 cm −1 represent the in-plane and out-of-plane bending of CO 3 2− , respectively. 37 Figure 2d shows that bands corresponding to SrCO 3 are not observed for either the as-prepared LSFCr powder or the LSFCr powder after exposure to 100% CO 2 at 30−800 °C, with a 24 h dwell time at 800 °C. However, at 1470 cm −1 , an asymmetric stretching band, corresponding to the C−O bond, was observed (Figure 2d(iii)).…”
Section: Resultsmentioning
confidence: 99%
“…We did not carry out x-ray crystallography in order to determine the crystal structure of the formed carbonates, because it already has been reported that even large organic additives, such as p-aminobenzioc acid, or N-(2-hydroxyethyl)ethylenediamine-N, N, N-triacetic acid did not change the crystal structure, and always the most stable orthorhombic strontionite [8].…”
Section: Resultsmentioning
confidence: 99%
“…Inorganic additives such as SiO 2 can also be used [7], and we have reported on the fabrication of dendritic, flower-like, and coral-like microcrystals in a SrCl 2 * This paper was presented at the 8th Asian Conference on Nanoscience and Nanotechnology (AsiaNANO 2016), Sapporo Convention Center, Sapporo, Japan, October 10-13, 2016. † Corresponding author: kart@photon.chitose.ac.jp ‡ Present address: Mitsubishi Polyester GmbH, Mainz, Germany / SiO 2 system [8]. In the present paper, we further focus on the control of the crystalline form by changing the conditions of crystal growth.…”
Section: Introductionmentioning
confidence: 99%